Clonal Micropropagation of Moringa oleifera Lam (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
Clonal micropropagation is an effective, modern method of accelerated vegetative propagation of plants and obtaining healthy, virus-free planting material. This study investigated the potential of using the tissue culture method to produce healthy Moringa (M.) oleifera Lam. planting material in vitro. Experiments were carried out using the tissue culture method. According to the results of the study in isolated culture, the efficiency of seed sterilization was found to be 85%. An optimal concentration of 0.5 mg/L gibberellic acid (GA3) was identified for seed germination on a Murashige-Skoog (MS) nutrient medium, achieving a germination efficiency of 80%. During clonal micropropagation, it was found that a half-strength (0.5) MS nutrient medium containing 0.2 mg/L indole-3-butyric acid (IBA) and 1.0 mg/L 6-benzyladenine (BAP) promoted the formation of up to six to eight micro-shoots from one explant. In in vitro culture on a 0.5 MS nutrient medium containing 0.1 - 0.5 mg/L IBA resulted in 98% rhizogenesis of micro-shoots and micro-cuttings. Micropropagated M. oleifera microplants exhibited 1.3 - 1.7 times higher growth intensity and 1.1 - 1.6 times more nodes at a concentration of 0.5 mg/L IBA than variants grown on 0.5 MS media with 0.1 - 0.4 mg/L IBA. For micropropagation of M. oleifera on a 0.5 MS medium, an IBA concentration of 0.3–0.5 mg/L was optimal, achieving a multiplication ratio of 1:5.
Keywords: In vitro; Gibberellic acid; Indole-3-butyric acid; Murashige-Skoog; Micro-shoots; Rhizogenesis